Numerical investigation of the water entry of cylinders without and with spin. (2nd February 2017) - Kiara, Areti; Paredes, Ruben; Yue, Dick K. P.
Abstract : We consider the water entry of horizontal cylinders with vertical impact velocity, either kept constant or freely falling, without and with spin, into quiescent water under the effect of gravity. We focus on the flow and cavity forming stages with non-dimensional submergence timet, Froude numbersFr, spin ratios[STIX]x1D6FC and mass ratiosm, all ofO(1) . We develop numerical simulations using a modified smoothed particle hydrodynamics method to obtain predictions for the impact kinematics and dynamics. These are in detailed agreement with available experiments. We elucidate the evolutions of the free surface, contact point positions, flow field, forces and trajectories and their dependence onFr, [STIX]x1D6FC andm . We define and quantify the contact point location[STIX]x1D703(t) as a function ofFr, clarifying the qualitative difference between sub- and supercriticalFr and the observed absence of air-entrained trailing cavities at lowFr . By subtracting the buoyancy associated with[STIX]x1D703(t), we show that, unlike the total drag, the remaining dynamic components are qualitatively similar for allFr . For a freely falling cylinder, we show that the total drag can be predicted from the constant velocity case with the same instantaneous velocity, providing a simple way to predict its trajectory based on the latter. The presence of spin results in lift, even when the asymmetry in[STIX]x1D703 is small. For fixed[STIX]x1D6FC, lift increases with subcriticalFr . For a freely falling cylinder, the lateral motion causes an appreciable asymmetry in[STIX]x1D703 and a reduction in lift.